2008
DOI: 10.1261/rna.1109808
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance placement of substrate RNA by H/ACA proteins

Abstract: The structural basis for accurate placement of substrate RNA by H/ACA proteins is studied using a nonintrusive fluorescence assay. A model substrate RNA containing 2-aminopurine immediately 39 of the uridine targeted for modification produces distinct fluorescence signals that report the substrate's docking status within the enzyme active site. We combined substrate RNA with complete and subcomplexes of H/ACA ribonucleoprotein particles and monitored changes in the substrate conformation. Our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…In the RNA-guided pseudouridylation reaction, the guide RNA uses its internal loop to capture substrate RNA through base-pairing. The four protein subunits all participate in the process of substrate RNA placement (Liang et al 2007(Liang et al , 2008(Liang et al , 2009). The protein subunits interact with the guide RNA in specific manners to tightly anchor it on the surface of Cbf5 such that the substrate RNA is correctly placed in the active site (Li and Ye 2006;Liang et al 2007Liang et al , 2009Duan et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the RNA-guided pseudouridylation reaction, the guide RNA uses its internal loop to capture substrate RNA through base-pairing. The four protein subunits all participate in the process of substrate RNA placement (Liang et al 2007(Liang et al , 2008(Liang et al , 2009). The protein subunits interact with the guide RNA in specific manners to tightly anchor it on the surface of Cbf5 such that the substrate RNA is correctly placed in the active site (Li and Ye 2006;Liang et al 2007Liang et al , 2009Duan et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al (25,42) employed fluorescence spectroscopy to monitor productive docking of the substrate RNA into the active RNP and found that L7Ae is a key player. Comparison of the crystal structures of the guide RNA-substrate RNA complex bound to Cbf5-Nop10 with (20,21) and without (25) L7Ae reveals markedly different RNA conformations.…”
Section: Role Of Proteins In Rna Remodelingmentioning
confidence: 99%
“…These data tentatively implicate Gar1 in product release. Fluorescence spectroscopic analysis of the RNP showed that whereas L7Ae promotes formation of the active structure of the RNP, Gar1 does the opposite (42). Gar1 may serve to stabilize the undocked inactive conformation of the RNP by biasing the thumb loop to its open conformation.…”
Section: Active Site and Enzymatic Turnovermentioning
confidence: 99%
“…The thumb loop of Cbf5, also called the β7_10 loop, is located between its β7 and β10 strands (Li and Ye 2006;Liang et al 2008Liang et al , 2009Duan et al 2009;Hamma and Ferré-D'Amaré 2010;Li et al 2011). It interacts with the Gar1 protein and the substrate RNA but not with the guide RNA.…”
Section: Introductionmentioning
confidence: 99%